2013
DOI: 10.1558/cj.v25i3.528-546
|View full text |Cite
|
Sign up to set email alerts
|

Web 2.0, Synthetic Immersive Environments, and Mobile Resources for Language Education

Abstract: In light of the increasingly blurred line between mediated and nonmediated contexts for social, professional, and educational purposes, attention to the presence and use of innovative digital media is critical to the consideration of the future of computer-assisted language learning (CALL). This article reviews current trends in the use of mediated communication and offers a vision for near-future second and foreign language (L2) learning that utilizes emerging media as (a) meaningful contexts for L2 language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
103
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(108 citation statements)
references
References 49 publications
0
103
0
5
Order By: Relevance
“…Studies focused on the effects of wikis as a tool for collaborative language learning have found considerable positive results. For instance, Sykes, Oskoz, and Thorne (2008) introduced wikis as a means of collaborative content building and dissemination of information, and wikis were described as a specific environment that utilizes collaborative tools in a study focused on the implementation of active and collaborative practices in information and communication technology classrooms. Lund and Rasmussen (2008) empirically examined how learners of senior high school English as a foreign language (EFL) approached and responded to an open-ended and collectively oriented task using a wiki and found that wikis helped learners to sustain strategies with many characteristics of collective production.…”
Section: Research On Wikis As a Tool For Language Learningmentioning
confidence: 99%
“…Studies focused on the effects of wikis as a tool for collaborative language learning have found considerable positive results. For instance, Sykes, Oskoz, and Thorne (2008) introduced wikis as a means of collaborative content building and dissemination of information, and wikis were described as a specific environment that utilizes collaborative tools in a study focused on the implementation of active and collaborative practices in information and communication technology classrooms. Lund and Rasmussen (2008) empirically examined how learners of senior high school English as a foreign language (EFL) approached and responded to an open-ended and collectively oriented task using a wiki and found that wikis helped learners to sustain strategies with many characteristics of collective production.…”
Section: Research On Wikis As a Tool For Language Learningmentioning
confidence: 99%
“…Today, the ubiquitous feature of e-learning makes learning and teaching through the Internet more convenient than ever before [1].With the potential benefits of elearning in language education, educational institutions and teachers devote significant efforts toward the applications of web-based curricula [2]. Using e-learning platforms, English learners can communicate and interact with other learners or native speakers with the target language in a time-saving and cost-effective way [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these serious games studies (23 of 39) deal with the technical possibilities and related instructional potentials of these games; proposals for serious game development and their integration into the FLL process; as well as learner/teacher attitudes towards digital games. Neville (2010) and Sykes, Oskoz, and Thorne (2008) introduce DGBLL in their works, explaining the advantages and disadvantages of serious games and make theoretical and instructional suggestions for game design and their integration into the classroom. Cai Miller, and Seneff (2013) and Rayner and Tsourakis (2013) are concerned with the use of language-technological components (such as speech-recognition and synthesis) in serious games.…”
mentioning
confidence: 99%